(untitled) (Journal of Imam Al-Kadhim College, 2025)
Among the foundational principles that have drawn the attention of Usul (Islamic legal theory) scholars since the early stages of its codification is the principle of Istishab (presumption of continuity). Jurists refer to this principle when no other evidence is found regarding a specific legal ruling. Usul scholars have cited reason (‘aql), rational practice (sīrah ‘uqalā’iyyah), consensus (ijmā‘), and traditions (akhbār) as proofs for the authority of Istishab. Among early scholars, the rational argument was considered the main evidence for its validity; hence, Istishab was classified as a speculative rational proof. This remains the dominant view among the majority. This study seeks to examine the narrative evidence supporting the principle of Istishab (presumption of continuity), through a comparative analysis between the Shi‘a Imami school and the other major Islamic jurisprudential schools. The Imami (Shi‘a) narrations concerning Istishab are numerous and diverse, and their hadith-based research is deep and detailed, involving extensive discussions of both the chains of transmission and the texts themselves. Therefore, I have classified the narrations into three categories, providing examples for each: The first (and most important) category includes narrations that explicitly provide a rationale based on the major premise of Istishab (“Certainty is never overruled by doubt”). The second category is similar in content to the first but lacks the explicit rationale. The third category supports Istishab indirectly through reference to the principles of purity (tahārah) or permissibility (hilliyyah). As for Sunni scholars, they were pioneers in using narrations to support the authority of Istishab. However, they did not comprehensively investigate the scriptural evidence. Instead, they cited one or two narrations without elaborating on how they indicate Istishab or to what extent they apply to legal rulings, given that they originally address specific legal subjects. While Sunni narrations are numerous, they are not diverse, resembling those of the second Imami category. They lack narrations comparable to the first and third Imami categories. Because Istishab was initially viewed as a speculative rational proof, scholars among the Sunni majority historically held differing views on its validity, both in classical and modern times. A similar trend existed among early Imami scholars. However, in the past three centuries, after Istishab came to be supported by narrations and these narrations became the primary evidence for its authority, the disagreement among Imami scholars ceased. Consequently, Istishab was reclassified from a speculative rational proof to a binding legal (religious) proof based on textual worship (ta‘abbud).